2022
DOI: 10.3390/jcm11154376
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Computed Tomography for Identifying Patients at High Risk of Endogenous Endophthalmitis Due to Klebsiella pneumoniae-Related Pyogenic Liver Abscess

Abstract: Endogenous endophthalmitis (EE) associated with Klebsiella pneumoniae (K. pneumoniae)-related pyogenic liver abscess (PLA) is one of the fatal complications of PLA and leads to loss of vision. Early diagnosis and treatment are important to save the patient’s vision. We investigated the characteristics of computed tomography (CT) in EE associated with K. pneumoniae-related PLA for the identification of the predictors of EE, in order to facilitate early diagnosis. A total of 274 patients diagnosed with K. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Hepatic abscesses rarely involve the portal vein or hepatic vein and cause thrombus forma-tion. However, several reports have indicated that liver abscesses caused by amoeba or Klebsiella pneumoniae more frequently involve the portal vein and hepatic vein [3][4][5]. In our case, we posit that a pseudoaneurysm caused by the liver abscess might have ruptured into the right hepatic vein or that the liver abscess invaded both the intrahepatic artery and right hepatic vein, resulting in an AVF.…”
Section: Discussionmentioning
confidence: 69%
“…Hepatic abscesses rarely involve the portal vein or hepatic vein and cause thrombus forma-tion. However, several reports have indicated that liver abscesses caused by amoeba or Klebsiella pneumoniae more frequently involve the portal vein and hepatic vein [3][4][5]. In our case, we posit that a pseudoaneurysm caused by the liver abscess might have ruptured into the right hepatic vein or that the liver abscess invaded both the intrahepatic artery and right hepatic vein, resulting in an AVF.…”
Section: Discussionmentioning
confidence: 69%
“…Since the gastrointestinal tract and the portal vein are linked, the pathogenic bacteria that cause liver abscesses primarily begin there. Diabetes mellitus and elderly male patients are most likely to develop abscesses [7,8].Due to the right lobe receives more blood ow volume, involvement of right lobe was predominant in liver abscesses(54.7%-82.7%) (Table 1 Persistent thrombocytopenia is related with poor prognosis in Intensive Care Unit (ICU) patients [21].The patient`s platelets count is pure Alice in wonderland. The number of platelets has dropped to 6 ×10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…13 In patients with K. pneumoniae-induced PLA, CT findings such as abscess location (i.e., left or both lobes) and involvement of adjacent vessels, in addition to ocular symptoms, should be considered for an early diagnosis of EE. 14 Treatment typically involves a combination of antibiotics and drainage of the abscess if necessary. K. pneumoniae was still highly susceptible to ceftazidime and amikacin, and the multidrug-resistant (MDR) K. pneumoniae isolates were not common in EE.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with K. pneumoniae ‐induced PLA, CT findings such as abscess location (i.e., left or both lobes) and involvement of adjacent vessels, in addition to ocular symptoms, should be considered for an early diagnosis of EE 14 . Treatment typically involves a combination of antibiotics and drainage of the abscess if necessary.…”
Section: Introductionmentioning
confidence: 99%